Thermal Field Analysis and Simulation of an Infrared Belt Furnace Used for Solar Cells. (12th May 2014) - Lu, Bai; Zongcun, Liang; Hui, Shen
Abstract : During solar cell firing, volatile organic compounds (VOC) and a small number of metal particles were removed using the gas flow. When the gas flow was disturbed by the thermal field of infrared belt furnace and structure, the metal particles in the discharging gas flow randomly adhered to the surface of solar cell, possibly causing contamination. Meanwhile, the gas flow also affected the thermal uniformity of the solar cell. In this paper, the heating mechanism of the solar cell caused by radiation, convection, and conduction during firing was analyzed. Afterward, four 2-dimensional (2D) models of the furnace were proposed. The transient thermal fields with different gas inlets, outlets, and internal structures were simulated. The thermal fields and the temperature of the solar cell could remain stable and uniform when the gas outlets were installed at the ends and in the middle of the furnace, with the gas inlets being distributed evenly. To verify the results, we produced four types of furnaces according to the four simulated results. The experimental results indicated that the thermal distribution of the furnace and the characteristics of the solar cells were consistent with the simulation. These experiments improved the efficiency of the solar cells while optimizing the solar cell manufacturing equipment.